Mitochondrial mutations in 12S rRNA and 16S rRNA presenting as chronic progressive external ophthalmoplegia (CPEO) plus: A case report. Issue 48 (December 2017) - Lv, Zhan-Yun; Xu, Xue-Mei; Cao, Xiao-Fu; Wang, Qian; Sun, Da-Fang; Tian, Wen-Jing; Yang, Yan; Wang, Yu-Zhong; Hao, Yan-Lei
Abstract: Rationale: Chronic progressive external ophthalmoplegia (CPEO) is a classical mitochondrial ocular disorder characterized by bilateral progressive ptosis and ophthalmoplegia. Kearns -Sayre syndrome (KSS) is a multisystem disorder with PEO, cardiac conduction block, and pigmentary retinopathy. A few individuals with CPEO have other manifestations of KSS, but do not meet all the clinical diagnosis criteria, and this is called "CPEO plus." Patient concerns: We report a 48-year-old woman exhibiting limb weakness, ptosis, ophthalmoparesis, and cerebellar dysfunctions. Diagnoses: The patient was diagnosed as exhibiting CPEO plus syndrome. Interventions: The patient underwent clinical, genetic, histological, and histochemical analysis. She was treated orally with CoQ10, vitamin Bs, L-carnitine, and vitamin E. Outcomes: The patient's serum creatine kinase levels, electrocardiography, and nerve conduction study results were normal; an electromyogram revealed myopathic findings. Magnetic resonance imaging showed global brain atrophy, particularly in the brainstem and cerebellum areas. A muscle biopsy showed the presence of abundant ragged red fibers. Sequencing of the mitochondrial DNA from the skeletal muscle biopsy revealed C960del mutation in 12S rRNA and homozygous mutation C2835T in 16S rRNA. She took medicines on schedule, the clinical features were similar as 2 years ago. Lessons: This is the first report of 2 rRNA mutations in a patient with MRI findings showing global brain atrophy, particularly in brainstem and cerebellum areas. Early recognition and appropriate treatment is crucial. This case highlights the cerebellar ataxia can occur in CPEO plus.